Perencanaan dan Pengendalian Proyek dengan Metode Pert - CPM Studi Kasus : Fly Over Ahmad Yani – Karawang - Anggara Hayun A (Bina Nusantara University, 2005)
The efficiency and effectivity is not a new guide in this global era. As a professional and innovative company, like consultant construction company that always makes customer satisfy, has a good achievement and reputation. There fore, efficiency and affectivity are necessary needed in a company. Article gives some inputs how to manage time become more effective and efficient in finishing project with CPM method. With using CPM method in “fly over project Ahmad Yani-Karawang”, is figured out the optimal time to finish this project which is 184 days.Keywords: